Expert Systems Development Through Software Product Lines Techniques - Cabello, María Eugenia; Ramos, Isidro (Information Systems Development, 2009)
This chapter deals with expert systems (ES) development as the final product of a software product line (SPL). We take into account software variability management in the ES domain. Two kinds of variability emerge: variability in the behavior as well as in the structure of such systems. Experts’ knowledge is captured using domain conceptual models in order to manage the variability and functionality of the ES. The ES are constructed using our baseline-oriented modeling (BOM) approach. BOM is a framework that automatically generates software applications as PRISMA architectural models by using SPL techniques. We follow the model-driven architecture (MDA) initiative for building domain models, which are automatically transformed into executable applications.